Analisis ayat-ayat tarbawi dalam surah al-baqarah menurut tafsir al-misbah dan relevansinya dengan tujuan pendidikan Islam - Nst, Rabiah Al-Husna; Erawadi, Erawadi; Harahap, Sumper Mulia (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This research aims to analyze the tarbawi verses in surah al-Baqarah according to Tafsir al-Misbah by M. Quraish Shihab and examine their relevance to the objectives of Islamic education in surah al-Baqarah verses 21, 30, 200, and 247 which contain fundamental educational values ​​in Islam. Using a qualitative-descriptive approach with literature study methods and content analysis. Tafsir al-Misbah is used as the main source in interpreting the meaning and values ​​of education. The results of the research show that these verses contain the basic principles of Islamic education, such as instilling faith and devotion to Allah SWT, becoming a caliph/leader, achieving happiness in the afterlife, forming Muslims with strong and noble morals. These values ​​are in line with the goals of Islamic education which include the formation of people who believe, have noble character, and are able to carry out the duties of the caliphate on earth. Thus, according to Tafsir al-Misbah, Surah al-Baqarah is relevant as a conceptual and practical basis in formulating the goals of Islamic education.